HUBUNGAN PENGGUNAAN MASKER SUNGKUP SELAMA TERAPI NEBULIZER TERHADAP SATURASI PERIFER OKSIGEN PADA PASIEN PPOK DI IGD BRSU TABANAN TAHUN 2016 - Sastro Putre Gustiawan; Adi Satriani; Ni Putu Kamaryati; Inca Buntari Agustini (Jurnal Riset Kesehatan Nasional, 2018)
Background. In Standard Operating Procedure, the use of hood mask on COPD patients in nebulizer therapy is used when necessary, which means that the medical staff able to wear a mask or not, it is because of lack of firmness in the Standard Operating Procedures created.Aim. To determine the relationship of the use of hoods during therapy nebulizer mask to saturation of peripheral oxygen in COPD patients in the ER Agency Tabanan General Hospital. Method. This research used non-probability sampling design, the sampling technique used in this study was consecutive sampling technique.Results. The respondents who wore hood mask on during nebulizer therapy as many as 84 respondents (98.8 percent), respondents who woremask on for 10-15 minutes by 85 respondents (100 percent), respondents who installed the rubber on mask during nebulizer therapy was 81 respondents (95.3 percent), the majority of respondents whom masks do did not come loose during nebulizer therapy as many as 76 respondents (89.4 percent). The saturation of oxygen peripheral therapy on COPD patients with nebulizer has a normal outcome as many as 82 respondents (96.5 percent).Conclusion. There was a significant relations between the use of hood mask during nebulizer therapy with the saturation of oxygen peripheral on COPD patients with the results of Pearson’s Chi-square test in Asymp.Sig value. (2-sided) of 0.00 (p = 0:00), because the value of Asymp.Sig. (2 -sided) 0:00 <0:05 (Alpha 5%).Suggestion. In a nebulizer therapy on COPD patients, medical staff should wear a hood mask during the therapy and follow-up the result of this study for the changes of standard operating procedures.Keywords:COPD, Hood Mask, Oxygen Peripheral Saturation, Nebulizer